Somali Poverty and Vulnerability Assessment : Findings from Wave 2 of the Somali High Frequency Survey - World Bank Group (World Bank, Washington, DC, 2019)
Somalia is on the path to political and security stabilization after more than two decades of civil war and conflict. Opportunities to ensure a development trajectory face many challenges since the country remains a fragile state subject to multiple shocks. Widespread poverty and food insecurity is a recurring developmental issue. Displacement is a key feature of modern Somali history linked to multiple drivers, including recurrent exposure to internal conflict and environmental hazards. Somalia is urbanizing rapidly due to large-scale forced displacement and economic migration that have driven large numbers of Somalis toward the urban areas. Remittances are central to the Somali economy and provide a lifeline to some segments of the population but not the most vulnerable. The World Bank implemented the second wave of the Somali high frequency survey (SHFS) in 2017-2018. This report is based on the most recent and first extensive household survey, wave 2 of the SHFS. The report is organized into six chapters. The first chapter presents an updated profile of monetary and nonmonetary dimensions of poverty for the Somali population, including the nomadic population. The second chapter explores in more detail spatial variation, with a focus on urbanization. The third chapter examines the impact of the 2016-2017 drought on livelihoods to identify the populations at risk and the factors that protected households against its negative effects. The fourth chapter provides an in-depth analysis of the internally displaced populations to identify displacement-related needs and to inform durable solutions. As a reaction to the analysis of poverty and vulnerabilities, the fifth chapter focuses on social protection as a means of promoting equity and building resilience against the effect of shocks on livelihoods. Similarly, the sixth chapter examines remittances and their role for livelihoods and resilience.